Ahmad Boestamam: tokoh radikal Melayu - Saat Ishak, Hadi Yaacob Norazlan, Ali Seman Ahmad, (Universiti Pendidikan Sultan Idris, 2016)
Ahmad Boestamam: tokoh radikal Melayu by Saat Ishak, Hadi Yaacob Norazlan, Ali Seman Ahmad,